Why is lexical retrieval slower for bilinguals? Evidence from picture naming. Issue 3 (26th December 2017) - SULLIVAN, MARGOT D.; POARCH, GREGORY J.; BIALYSTOK, ELLEN
Abstract : Proficient bilinguals demonstrate slower lexical retrieval than comparable monolinguals. The present study tested predictions from two main accounts of this effect, the frequency-lag and competition hypotheses. Both make the same prediction for bilinguals but differ for trilinguals and for age differences. 200 younger or older adults who were monolingual, bilingual, or trilingual performed a picture naming task in English that included high and low frequency words. Naming times were faster for high than for low frequency words and, in line with frequency-lag, group differences were larger for low than high frequency items. However, on all other measures, bilinguals and trilinguals performed equivalently, and lexical retrieval differences between language groups did not attenuate with age, consistent with the competition view.